Epidemiology of highly adaptable clones: ST398 and human diseases - Abraão, Lígia Maria [UNESP]; Bonesso, Mariana Fávero [UNESP]; Pereira-Franchi, Eliane Patrícia Lino [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (My University, 2021)
Staphylococcus aureus still remains as one of the most important pathogens widely disseminated among both hospitals and community settings. Interestingly, recent reports have shown that some S. aureus strains are highly adaptable and can jump from humans to animals and to humans again after regaining new resistance and virulence factors. Here we present an epidemiological overview of those strains focusing mainly on ST398, since it is becoming an important infectious agent among humans. Noteworthy, ST398 was considered an important livestock-associated pathogen that could be transmitted to humans and only recently emerged in humans related infections highly virulent. Since S. aureus is widely disseminated, other clonal complexes are rising and adapting fast. Furthermore, we will highlight the main epidemiology behind this tricky pathogen and pose an important question: is it molecular epidemiology enough to protect us from S. aureus future dissemination?